Boncuklu Tarla (Mardin), Turkey. Near Eastern Neolithic Architecture (NENA). The case of Boncuklu Tarla. Season 2021 - Kinzel, Moritz (e-Forschungsberichte des DAI, 2022)
Despite the fact that the architecture is one of the most prominent features of the Near Eastern Neolithic, there has not yet been a well-established research group dealing with it. This desideratum has prompted us to initiate NENA to exchange findings, interpretations, terminologies, technologies and sites. As part of NENA, excavation projects are supported in the field to document and study Neolithic architecture. In this framework an early Neolithic building at Boncuklu Tarla/Southeast-Turkey was investigated in 2021.